Real-time speech MRI: Commercial Cartesian and non-Cartesian sequences at 3T and feasibility of offline TGV reconstruction to visualise velopharyngeal motion. (February 2018) - Freitas, Andreia C.; Ruthven, Matthieu; Boubertakh, Redha; Miquel, Marc E.
Highlights: Increase clinical reliability of real-time MRI in speech assessment. Cartesian and non-Cartesian rt-MRI in temporal resolution/image quality compromise. Feasibility of accelerated radial imaging and offline iterative reconstruction. Abstract: Purpose: This study aims to improve clinical reliability of real-time Magnetic Resonance Imaging (rt-MRI) in the visualisation of velopharyngeal motion during speech. Methods: Seven subjects were imaged at 3T during natural phonation. Speech rt-MRI methodologies were investigated with (i) a comparison of commercial Cartesian and non-Cartesian (radial and spiral) rt-MRI sequences and (ii) investigation of further improvement with accelerated radial acquisition and offline reconstruction methodology. Results: Cartesian and non-Cartesian protocols were implemented with temporal resolutions between 10 frames per second (fps) and 27 fps and voxel sizes between 1.5 × 1.5 × 10 mm 3 and 2.7 × 2.7 × 10 mm 3 . Commercial spiral acquisitions provided superior contrast-to-noise ratio (CNR) than otherwise equivalent Cartesian and radial. Spirals at 22 fps allowed for improved spatial resolution (1.9 × 1.9 mm 2 ) when compared to similar Cartesian protocols (20 fps), limited to a lower spatial resolution (2.7 × 2.7 mm 2 ). Cartesian protocols were on average scored higher than spiral protocols in visual quality. However, some variability was found on choice of recommended imaging protocol between subjects. Accelerated radial data reconstructed offline with a Total Generalized Variation (TGV) scheme showed improved visual sharpness of velum motion. Discussion/Conclusion: Adequate visualisation of velopharyngeal motion with commercial rt-MRI at 3T was possible. Both Cartesian and spiral protocols demonstrated adequate temporal depiction and overall image quality. However, choice of optimal imaging protocol at 3T was more subject-dependent than in previously published 1.5T data and additional care should be taken when selecting an adequate protocol. Offline TGV reconstruction of radial data has shown potential to improve temporal sharpness.